Strategi Bank Syariah dalam Mempertahankan Loyalitas Konsumen : (Pada PT. BSI KCP Bukittinggi Sudirman) - Fitriani Fitriani; Jon Kenedi (Transformasi: Journal of Economics and Business Management, 2024)
This research is motivated by an interesting phenomenon in the field where it is difficult for Sharia Banks to maintain customer loyalty because many customers switch to other banks due to the public's lack of knowledge of Sharia Banking. This research aims to find out the strategies or methods used by Bank Syariah Indonesia KCP Bukitinggi Sudirman in maintaining consumer loyalty so that consumers do not move to other banks which has an impact on decreasing financing achievements and collections can decrease, so an analysis of the strategies implemented by Bank Syariah KCP is needed. Bukitinggi Sudirman using SWOT analysis, namely strengths, weaknesses, opportunities and threats. This research is descriptive qualitative in nature and data collection methods are interviews, observation and documentation. Meanwhile, the technical data analysis used by researchers is SWOT analysis, IFE Matrix analysis, EFE Matrix, SWOT Matrix and Score Weight Table analysis. From the results of the research carried out, the strategy that can be implemented in maintaining consumer loyalty at BSI KCP Bukitinggi Sudirman is by using the SO strategy, namely offering a competitive ratio or profit sharing value based on special banking regulations for sharia banks and the strength of the LPS (deposit insurance agency), improving quality. services, socializing bank products (financing) so that they are more easily understood and accepted by the public.